Advancements in Optical Current Sensors for High Power Systems: A Comprehensive Review - Pandey, Dr. Badri Narayan; Kumar, Sumit (Journal of Advanced Research in Geo Sciences & Remote Sensing, 2023)
A new generation of smart grids may find the inherent benefits of optical sensor technology to be highly useful. These benefits are especially attractive for high voltage applications. A review of optical sensor technologies for electrical current metering in high voltage applications is provided by the authors in this publication. Along with a more in-depth focus on contemporary developments, a brief historical summary is provided. All fibre sensors, bulk magneto-optical sensors, piezoelectric transducers, magnetic force sensors, and hybrid sensors are among the technologies covered. The fundamental benefits and drawbacks of physical concepts are explained. Configurations and methods to deal with issues such magnetic field-induced linear birefringence, interference from outside currents, and others are described. The most recent technology, including commercially available systems, is given.